PENGARUH PARTISIPASI ANGGARAN, KEADILAN PROSEDURAL, KEADILAN DISTRIBUTIF, DAN GOAL COMMITMENT PADA KINERJA ORGANISASI - Wiryanata, I Gusti Ngurah Agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.03.N0.01.TAHUN 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The results of previous studies on the effect of budgetary participation, procedural fairness, distributive fairness and goal commitment to organization's performance are inconsistent, therefore this study tried to investigate them again. The data used in this research was primary data that were collected using a set of questionnaire. The analysis technique used was linear regression analysis. The results of this study showed that: budgetary participation, procedural fairness, distributive fairness, and goal commitment positively influenced the organizational performance. It statistically indicated that the better the budgetary participation, procedural fairness, distributive fairness, and goal commitment, hence the performance of organization increased.
Keywords: partisipasi anggaran, keadilan, goal commitment, kinerja